Review of World Rugby`s Test Method 01 head injury criteria: Procedure analysis and optimisation - Colino, E.; Felipe, J. L.; Douglas, M.; Harrison, E.; Webb, C.; del Corral, J.; Gallardo, L.; Garcia-Unanue, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2026)
Rugby is a close-contact sport in which players occasionally fall headfirst to the ground during scrums and tackles. Because head impacts represent an obvious threat to players` integrity and safety, World Rugby, Rugby`s International Governing Body, developed a test method named Test Method 01 to evaluate the capacity of the playing surface to mitigate head impacts by determining the critical fall height (CFH). The aim of this study is to analyse World Rugby`s current Test Method 01 head injury criteria (HIC), which consider a field as unsafe if the CFH is below 1.3 m. To make this analysis, a pilot study was performed on seven artificial turf rugby fields. At each field, a three-drop procedure was performed to estimate the initial CFH (CFH0). Subsequently, the procedure was repeated on each surface at 50-mm intervals, from 0.6 m below to 0.6 m above CFH0. All possible combinations of four height-HIC data pairs with two height values below and above 1000 HIC were obtained. A comparison was performed between the linear adjustment, currently prescribed in Test Method 01 to calculate the CFH0, and the quadratic adjustment. In particular, the percentage of outliers obtained when applying both the linear and quadratic adjustment and the robustness of the regressions were investigated. The results show that the current Test Method 01 can be improved by applying two main modifications: first, replacing the linear adjustment with a quadratic adjustment, and second, adapting the current test restrictions by maintaining the maximum difference between the highest and the lowest drop heights in 1.00 m, increasing the minimum difference between consecutive drop heights from 0.15 to 0.20 m and removing the current prohibition on obtaining HIC values close to 1000.